Organizational Justice and Affective Organizational Commitment: Mediated by Organizational Trust and Perceived Organizational Support - Hayunintyas, Ruri Fitria; Do, Ben Roy; Sudiro, Achmad; Irawanto, Dodi Wirawan (Department of Management, Faculty of Economics and Business, Brawijaya University, 2018)
Organizational justice refers to employee perceptions of fairness of treatment by the organization, and their behavioral reactions to this justice. Based on social exchange theory, one consequence of organizational justice is organizational trust, the willingness to invest one's resources in a relationship resulting from positive expectations as a consequence of previous interaction. Another consequence of organizational justice is perceived organizational support (POS), the extent to which employees feel their contribution is valued by the organization, and the organization cares about their well-being and gives fair treatment. All three variables may contribute to affective organizational commitment. To test the mediation of organizational trust and POS, 188 valid questionnaires were analyzed in a large company of poultry industry in Indonesia. All research hypotheses were supported, where it is practically important that organization in this context to address the practice of organizational justice with the support of organization in term of trust and managerial support in creating organizational commitment.